Nietoperz karlik malutki Pipistrellus pipistrellus (Schreber 1774) w faunie Puszczy Białowieskiej - Rachwald, Alek; Ruczyński, Ireneusz (Leśne Prace Badawcze, 2026)
The occurrence of the Common pipistrelle in the bat fauna of the Białowieża Primeval Forest was expected, because the taxon P. pipistrellus was previously comprised of two separate species. Earlier observations of P. pipistrellus in the Białowieża area can mostly be counted for by the new species Soprano pipistrelle, which is considered equally widely distributed in the area. In this study, we were able to record and distinguish several passes of the Common pipistrelle by means of bat detecting techniques. Bats were found in two locations, the first one being the Białowieża village, whereas the second one is the woodland in close proximity of the Czerlonka village. It is very likely, that this species is more widely distributed in the Białowieża area, especially in the vicinity of human settlements.